Mothers' perceptions of self‐efficacy and satisfaction with parenting are related to their use of controlling and positive food parenting practices. Issue 1 (15th September 2021) - Holley, Clare E.; Haycraft, Emma
Abstract: Perceptions of parenting competence are composed of self‐efficacy and satisfaction with parenting. Parenting competence is linked to differential outcomes across numerous parenting domains. To date, few studies have explored the relationships between maternal self‐efficacy and food parenting practices, deploying different measures and age ranges, and yielding conflicting findings. Therefore, the current study sought to explore relationships between the two dimensions of perceived parenting competence and the use of controlling and positive food parenting practices. UK mothers ( N  = 269) of 18‐ to 59‐month‐old children completed measures of both dimensions of perceived parenting competence (i.e., parenting self‐efficacy and satisfaction) and of controlling (maladaptive) and positive (health promoting) food parenting practices. Relationships were found between perceptions of competence and use of food parenting practices. Self‐efficacy and satisfaction with parenting were positively associated with the use of most positive food parenting practices. Greater parenting satisfaction, but not parenting efficacy, was associated with lower use of some of the potentially detrimental controlling food parenting practices. Neither parenting self‐efficacy nor satisfaction with parenting were related to mothers' reported use of pressure to eat. In conclusion, supporting and promoting greater maternal self‐efficacy and satisfaction with parenting may be a useful target for public health interventions and for professionals working with families with the aim of promoting optimal parenting to support children's development of healthy eating habits. Future research should seek to further elucidate the current findings with a longitudinal design.